Lactobacillus paracasei improves dietary fatty liver by reducing insulin resistance and inflammation in obese mice model. (August 2022) - Ji, Yaoyao; Xie, Qiang; Meng, Xiangren; Wang, Wei; Li, Shengnan; Lang, Xinsong; Zhao, Changhui; Yuan, Yuan; Ye, Haiqing
Graphical abstract: Highlights: Jlus66 is a Lactobacillus paracasei isolated from natural fermented dairy products. Jlus66 could alleviate insulin resistance and inflammatory response in liver. Jlus66 could attenuate jejunum leakage, inflammation and oxidative stress. Jlus66 could improve lipid metabolism disturbances in adipose tissue. Abstract: Long term high-fat diet (HFD) will lead to obesity and its complications, such as lipid metabolism disorder, insulin resistance and inflammation. The purpose of this study is to demonstrate the mechanism of Lactobacillus paracasei Jlus66 to improve dietary fatty liver in obese mice model. C57BL/6J male mice were randomly divided into three groups (Control, HFD and HFD + Jlus66). Proteins of many pathways related to insulin resistance (IRS-1, AKT, GSK3β, GLUT4 and PTP1B), to jejunum permeability (Zo-1, Claudin-1 and Occludin) were detected by using western blotting. Correspondingly, genes of inflammation ( Inos, Tnf-α and Il-1β ), mitochondrial dysfunction ( Cox5b, Cox7a1, CoxⅡ, Cox8b, Cycs and Sirt1 ) and oxidative stress ( yGcs, Mnsod, Nqo-1, Gpx1 and Ho-1 ) were detected by using RT-qPCR. As results, Jlus66 effectively improved lipid metabolism disorder and mitochondrial dysfunction, ameliorated insulin resistance and inflammatory response in the liver, jejunum and adipose tissue of HFD-induced obese mice model. Moreover, Jlus66 treated also protected jejunum barrier integrity and alleviated oxidative stress. In conclusion, Jlus66 might be a nutritional strategy for obesity and its complications.